Akad Qardl Hasan sebagai Solusi Ekonomi Kerakyatan - Subaidi Subaidi; Ahmad Muzakki (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2019)
Qardl hasan is the treasure given by the debt provider (muqridh) to the debt recipient (muqtaridh) then to be returned to them (muqridh) according to the amount received when he has been able to pay without obligation to pay interest or other benefits, because in qardl actually there is no clause with coercion where one side does not abuse the other. Muqtaridh is only burdened with paying off debts as big as the loan within a certain period. However, muqtaridh is recommended to return the better of debts to muqridh. Because the essence of qardl hasan is to reward Allah for Islamic interests, and of course the repayment is not same as the repayment made by humans. In this case of Islamic banking represented by Bank Muamalat Indonesia has completely arranged matters relating to qardl hasan which are generally in accordance with the rules in fiqh. If qardl hasan is implemented properly and those distributions of funds can reach all levels of middle to lower class in society, so it will be the solution for the economic progress in society.